Poverty Reduction through Local Financial Performance: Case Study in East Nusa Tenggara Province, Indonesia - Endang Mahpudin (Universitas Muhammadiyah Ponorogo, 2020)
The high level of poverty in East Nusa Tenggara Province, Indonesia, requires effort to be alleviated. For instance, there is a need to enhance the financial management performance of the locals. Therefore this study analyzes the contribution of local financial performance to the poverty rate. It uses panel data regression analysis involving 22 regencies and municipalities from 2015 to 2018. The results of the study showed that the local financial independency ratio in various regencies and municipalities has fewer contributions to the poverty rate. Local governments need to increase regional fiscal capacity integrated with efforts to improve regional macroeconomic performance. Moreover, they should increase alignments toward poverty alleviation programs as well as the capacity of regional apparatus.